2022
DOI: 10.3390/app12104957
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study on the Mechanical Activation and High-Temperature Treatment of Saponite-Containing Tailings Generated during Kimberlite Ore Dressing

Abstract: This study investigates transformations of a pre-mechanically activated saponite-containing material with subsequent high-temperature treatment. The thermogravimetric analysis confirmed that the mechanical activation of saponite leads to the destruction of its layered structure, accompanied by the release of silicon dioxide and magnesium oxide in free form. The values of surface activity for mechanically activated saponite-containing material are also calculated. It is shown that when mechanically activated sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(15 reference statements)
1
2
0
Order By: Relevance
“…The performed investigation results became the basis for the development of a technological scheme for the production of composite nitrogen-phosphorus-potassium containing NPK fertilizers, using also expanded vermiculite to ensure a prolonged action of the resulting fertilizers (Figure 13). The results of the studies performed in this work are consistent with the results published by other researchers in the works [55,[65][66][67][68][69][70][71][72].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The performed investigation results became the basis for the development of a technological scheme for the production of composite nitrogen-phosphorus-potassium containing NPK fertilizers, using also expanded vermiculite to ensure a prolonged action of the resulting fertilizers (Figure 13). The results of the studies performed in this work are consistent with the results published by other researchers in the works [55,[65][66][67][68][69][70][71][72].…”
Section: Discussionsupporting
confidence: 92%
“…The authors of several papers [55][56][57][58] have shown that significant structural changes occur in the process of mechanochemical activation, leading to an increase in reactivity and an improvement in the solubility of mechanochemically activated substances.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical activation is applied in the following industrial fields: mechanical alloying, preparation of ores, leaching of ores and extractive metallurgy, sintering of materials, manufacture of pigments and paints, manufacture of pharmaceutical and geopolymers products to which new areas of application are constantly being added. [99][100][101][102][103].…”
Section: Fig 1 Phase Transitions Of Alumina Mineralogical Phases [93]mentioning
confidence: 99%